On the behavior of solutions of linear functional differential equations with constant coefficients and linearly transformed argument in neighborhoods of singular points - Bel’skii, D. V.; Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We establish new properties of C^1 (0, + ∞)-solutions of the linear functional differential equation x(t) = ax(t) + bx(qt) + cx(qt) in the neighborhoods of the singular points t = 0 and t = + ∞.